Analysis of Management of Santri Mini Bank (BMS) on Quran Memorization Institute Foundation Islamic Centre North Sumatra - Margolang, Yusrinaldi Rahman; Rahmayati (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The purpose of this study is to analyze financial managementSantri Mini Bank (BMS) inQuran Memorization Center FoundationIslamic Center of North Sumatra. BMS is here as a solution to students' financial problems, such as sending funds from guardians and the risk of losing money.The methods used are those that have a case study approach through interviews, observations and documentation. The results showThe manual system creates operational challenges such as queues and delays in disbursement of funds. Digitization through e-money and information technology-based record-keeping is recommended to improve efficiency, transparency, and accountability. With the right strategy, BMS has the potential to become a secure and educational financial system for Islamic boarding school students.